Proteomics-Based Characterization of miR-574-5p Decoy to CUGBP1 Suggests Specificity for mPGES-1 Regulation in Human Lung Cancer Cells - Emmerich, Anne C.; Wellstein, Julia; Ossipova, Elena; Baumann, Isabell; Lengqvist, Johan; Kultima, Kim; Jakobsson, Per-Johan; Steinhilber, Dieter; Saul, Meike J. (Frontiers in Pharmacology, 2020)
MicroRNAs (miRs) are one of the most important post-transcriptional repressors of gene expression. However, miR-574-5p has recently been shown to positively regulate the expression of microsomal prostaglandin E-synthase-1 (mPGES-1), a key enzyme in the prostaglandin E2 (PGE2) biosynthesis, by acting as decoy to the RNA-binding protein CUG-RNA binding protein 1 (CUGBP1) in human lung cancer. MiR-574-5p exhibits oncogenic properties and promotes lung tumor growth in vivo via induction of mPGES-1 derived PGE2 synthesis. In a mass spectrometry-based proteomics study, we now attempted to characterize this decoy mechanism in A549 lung cancer cells at cellular level. Besides the identification of novel CUGBP1 targets, we identified that the interaction between miR-574-5p and CUGBP1specifically regulates mPGES-1 expression. This is supported by the fact that CUGBP1 and miR-574-5p are located in the nucleus, where CUGBP1 regulates alternative splicing. Further, in a bioinformatical approach we showed that the decoy-dependent mPGES-1 splicing pattern is unique. The specificity of miR-574-5p/CUGBP1 regulation on mPGES-1 expression supports the therapeutic strategy of pharmacological inhibition of PGE2 formation, which may provide significant therapeutic value for NSCLC patients with high miR-574-5p level.